Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P.; Ruiz-Fons, F.; Vicente, J.; Reyes-García, a R.; Alzaga, V.; Gortázar, C. (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P; Ruiz-Fons, F; Vicente, J; Reyes-García, a. R; Alzaga, V; Gortázar, C (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates